Pengaruh Modal Kredit Usaha Rakyat (KSP Kopdit Obor Mas Cabang Utama Nagekeo) Terhadap Pendapatan Pelaku Usaha Mikro Kecil Dan Menengah Pada Sektor Pertanian Di Kecamatan Aesesa Kabupaten Nagekeo - Martina Owa; Andreas Rengga; Konstantinus Pati Sanga (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This research aimed to analyze the effect of people’s Business Credit Capital (Obor Mas Nagekeo Credit union) on the income of MSMEs actors enterprises in the agricultural sector in Aesesa sub – district, Nagekeo regnency. The analyze method used used simple linear method testing. Based on the results of linear regression testing in this research, Y=27,694,720,080 + 0.462 X. means that when the people’s Business Credit Capital Variable (X) increased by one unit, the MSMEs Actors Income Variable (Y) increased by 0.462. the results of the calculation of the regression coefficient showed that the R Square value was o,366 or 36,6%, meaning that the people’s Business Credit Capital Variable (X) could explain the income of MSMEs actors (Y) by 36,6% and the rest was explained by other variables not used in this research model.